Local maize; a contextualization of traditional indentity - Guevara-Hernández, Francisco; Hernández-Ramos, Manuel Antonio; Basterrechea-Bermejo, José Luis; Pinto-Ruiz, René; Venegas-Venegas, José Apolonio; Rodríguez-Larramendi, Luis A.; Cadena-Iñiguez, Pedro (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2019)
This article rises at a first glance on the how important is to agree on an integrative concept for the diversity richness of the maize species and currently grown and preserved in different agroecological and cultural contexts of Mexico, and arises as a conceptual necessity for research project about maize and its multiple purpose uses. The article is proposed due to the current confusion between some concepts and definitions usually read and heard in academic vocabulary regarding the maize. This proposal is made from a literature review of academic documents; with an ethnoagronomic and holistic approach of conceptual integration on the use, management and conservation of maize. Classic and recent academic information was used to decipher and point out the trends in the nomenclature (concepts and definitions) used to name the types of maize currently grown. In conclusion, it is proposed that the maize grown mainly in rural communities could be called "local maize", especially those that are used from the integration of cultural, genetic and phenotypic components or that originate as a result of continuous use, management and conservation in those niches where they can be found.